Chemical Constituents From Annona Muricata (Linn.) and Garcinia Mangostana (Linn.) and Their Biological Activities - Daud, Shaari (2005)
Chemical studies were carried out on Annona muricata L. (Annonaceae) and Garcilzia mangostana L. (Guttiferae). The chemical investigations covered acetogenin, triterpenoids and xanthones. These compounds were isolated using common chromatographic techniques and were identified by using spectroscopic technique such as NMR, MS, IR and UV. Biological activities for both plants were also evaluated for their antimicrobial activities against four pathogenic bacteria and four fungi, cytotoxic activity against CEM-SS and HL-60 cell lines and larvicidal activity against Aedes aegypti. Larvicidal activity data have never been reported before.Annona muricata L. (stem bark) have afforded one acetogenin, solamin and two triterpenoids, stigmasterol and sitosterol. Meanwhile studies on Garcinia mangostana L. (bark) have provided a new xanthone, mangosharin (2,8-dihydroxy-6-methoxy-5-(3- methylbut-2-eny1)-xanthone) together with six other xanthones, a-mangostin, Pmangostin, garcinone D, xanthone 1, 1,6-dihydroxy-3,7-dimethoxy-2-(3-methylbut-2- eny1)-xanthone and mangostanol and one triterpenoid, friedelin. Cytotoxic tests were performed using CEM-SS cell line and HL-60 cell line. The crude hexane extract of Annona muricata L. gave a significant activity with an IC50 value of 0.8 pg/ml against CEM-SS cell line while the crude ethyl acetate (EA) extract also gave a significant activity with an IC5v~a lue of 0.5 pg/ml but against HL-60 cell line. The crude hexane extract of Garcinia mangostana L. is also considered to be active against the CEM-SS cell-line with an IC50 value of 17 pg/ml. Other than that, the pure compounds a-mangostin, mangostanol and garcinone D also gave significant activities with ICso values of 5.5,9.6 and 3.2 pg/ml against CEM-SS cell line, respectively. The antimicrobial activity test was also carried out using four pathogenic bacteria, namely, Methicillin Resistant Staphylococcus aures, Pseudomonas aeruginosa, Salmonella typhimurium and Bacillus subtilis. However, most of the crude extracts gave only moderate or weak activity. The pure compound a-mangostin gave weak activity against Salmonella typhimurium and medium inhibition against Bacillus subtilis.The larvicidal tests were performed against the larvae of Aedes a e m i using the WHO (1981) standard procedures with slight modifications. The crude hexane and ethyl acetate extracts of Annona muricata L. showed moderate toxicity towards the larvae by giving LCSO values of less than 100 pg/ml. The crude hexane and ethanol extracts of Garcinia mangostana L. gave weak activities against the larvae with LCso values of more than 150 pglml while the crude ethyl acetate extract showed moderate activity with an LC5() value of 30.1 pg/ml. Larvacidal activity on the pure compound, a-mangostin gave a LCs0 value of 19.4 pglml. No activity was recorded for the antihgal activity tests